ASSESSING SNACK FOOD MANUFACTURERS’ CONFORMITY TO THE LAW ON FOOD LABELLING - Yuhanza Othman; Zuhairah Hasan; Mimi Sofiah Mustafa; Ida Rahayu Mahat; Marziana Abd Malib (International Journal of Accounting, Finance and Business, 2021)
Food labelling is one of the methods used by food manufacturers to communicate to consumers concerning their product. Nevertheless, food manufacturers cannot simply label their products based on their convenience. This is because the Food Act 1983 provides that those who fail to comply with any prescribed food standard commit an offence. The Ministry of Health through delegated power given by Section 34 of the Food Act 1983 has introduced the Food Regulation 1985 to prescribe the labelling particulars. Despite these two laws, there are cases where food manufacturers fail to follow food labelling regulations. Besides, the wording and the label used are confusing the consumers. Thus, this research was conducted to assess the food manufacturers’ conformity with the law of food labelling. The subject matter of this study is a snack food that is categorised into sweet, chocolate, chips, crackers, biscuit and nuts. A convenience sampling method was used where the snack foods were purchased from groceries shop in Melaka and all data collected were analysed in SPSS. This study on food labelling is significant toward the consumers’ safety and at the same time would benefit the food manufacturers in marketing their products.